Facile Synthesis of Polycyclic Aromatic Hydrocarbons: Brønsted Acid Catalyzed Dehydrative Cycloaromatization of Carbonyl Compounds in 1, 1, 1, 3, 3, 3‐Hexafluoropropan‐2‐ol. Issue 2 (6th December 2016) - Fujita, Takeshi; Takahashi, Ikko; Hayashi, Masaki; Wang, Jingchen; Fuchibe, Kohei; Ichikawa, Junji
Abstract : The cycloaromatization of aromatic aldehydes and ketones was readily achieved by using a Brønsted acid catalyst in 1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐ol (HFIP). In the presence of a catalytic amount of trifluoromethanesulfonic acid, biaryl‐2‐ylacetaldehydes and 2‐benzylbenzaldehydes underwent sequential intramolecular cationic cyclization and dehydration to afford phenacenes and acenes, respectively. Furthermore, biaryl‐2‐ylacetaldehydes bearing a cyclopentene moiety at the α‐position underwent unprecedented cycloaromatization including ring expansion to afford triphenylenes. HFIP effectively promoted the cyclizations by suppressing side reactions presumably as a result of stabilization of the cationic intermediates. Abstract : The cycloaromatization of aromatic aldehydes and ketones is readily achieved by using a Brønsted acid catalyst in 1, 1, 1, 3, 3, 3‐hexafluoropropan‐2‐ol. In the presence of a catalytic amount of trifluoromethanesulfonic acid (TfOH), biaryl‐2‐ylacetaldehydes and 2‐benzylbenzaldehydes undergo sequential intramolecular cationic cyclization and dehydration to afford polycyclic aromatic hydrocarbons.